Peningkatan Kadar Nikel Dalam Laterit Jenis Limonit Dengan Cara Peletasi, Pemanggangan Reduksi Dan Pemisahan Magnet Campuran Bijih, Batu Bara, Dan Na2SO4 [Upgrading of Nickel Content in The Limonitic Laterite Ores by Pelletizing, Reduction Roasting and Magnetic Separation of The Mixed Ores, Coal and Sodium Sulphate] - Rudi Subagja; Agus Budi Prasetyo; Wahyu Mayang Sari (National Research and Innovation Agency (BRIN), 2016)
In Indonesia, laterite nickle ore that is low grade nickel (<1.5%) has not been used well because it is not considered beneficial. At present work, the experiment to increase nickel grade in the limonitic type of laterite ores has been caried out by pelletizing a limonitic type of laterite ores, coal and Na2SO4 mixture, it was followed with reduction roasting of pellet in muffle furnace at temperatues 800 ºC to 1100 ºC and reduction roasting time from 0,5 hours to 4 hours. The reduced ore from reduction roasting process was grounded in vibrating mill, then mixed with water and passed to magnetic separator to separate nickel concentrates from the tailing. The concentrate with 10.28% of nickel grade and 66,57% of iron grade was produced from hour, 10 % of coal addition and 20% of Na2SO4 addition with recovery of nickel and iron in the consentrate 64,77% and 34,66% respectively.AbstrakPada penelitian ini telah dilakukan percobaan untuk meningkatkan kadar nikel dalam bijih nikel laterit jenis limonit dengan cara membuat pelet dari campuran bijih nikel laterit jenis limonit, batubara dan natrium sulfat, dilanjutkan dengan pemanggangan reduksi pelet dalam tungku mufle pada temperatur 800 0 C sampai dengan 1100 o C dan waktu pemanggangan reduksi dari 0,5 jam sampai dengan 4 jam. Kalsin yang dihasilkan dari proses pemanggangan kemudian digiling dalam vibrating mill untuk selanjutnya dicampur dengan air dan dilewatkan kedalam alat pemisah magnet sehingga dihasilkan konsentrat dan tailing. Konsentrat dengan kadar nikel 10,28 % dan kadar besi 66,57 % diperoleh dari kalsin hasil proses pemanggangan reduksi pada temperatur 1000 o C selama 1 jam, penambahan batubara 10 % dan penambahan natrium sulfat 20 %, dimana perolehan nikel dan besi dalam konsentrat masing masing adalah 64,77 % dan 34,66 %